Evolution of Fetal Growth in Symptomatic Sars-Cov-2 Pregnancies - Hachenberg, Jens; Guenther, Julia; Steinkasserer, Lena; Brodowski, Lars; Dueppers, Ansgard Lena; Delius, Maria; Chiaie, Loredana Delle; Lobmaier, Silvia; Sourouni, Marina; Richter, Manuela F.; Manz, Jula; Parchmann, Olaf; Schmidt, Saskia; Winkler, Jennifer; Werring, Pia; Kraft, Katrina; Kunze, Mirjam; Manz, Maike; Eichler, Christian; Schaefer, Viola; Berghaeuser, Martin; Schlembach, Dietmar; Seeger, Sven; Schäfer-Graf, Ute; Kyvernitakis, Ioannis; Bohlmann, Michael K.; Ramsauer, Babette; Morfeld, Christine Angela; Ruediger, Mario; Pecks, Ulrich; von Kaisenberg, Constantin (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Introduction SARS-CoV-2 is a viral disease with potentially devastating effects. Observational studies of pregnant women infected with SARS-CoV-2 report an increased risk for FGR. This study utilizes data from a prospective SARS-CoV-2 registry in pregnancy, investigating the progression of fetuses to fetal growth restriction (FGR) at birth following maternal SARS-CoV-2 and evaluating the hypothesis of whether the percentage of SGA at birth is increased after maternal SARS-CoV-2 taking into account the time interval between infection and birth.Materials & Methods CRONOS is a prospective German registry enrolling pregnant women with confirmed SARS-CoV-2 infection during their pregnancy. SARS-CoV-2 symptoms, pregnancy- and delivery-specific information were recorded. The data evaluated in this study range from March 2020 until August 2021. Women with SARS-CoV-2 were divided into three groups according to the time of infection/symptoms to delivery: Group I<2 weeks, Group II 2–4 weeks, and Group III>4 weeks. FGR was defined as estimated and/or birth weight<10% ile, appropriate for gestational age (AGA) was within 10 and 90%ile, and large for gestational age (LGA) was defined as fetal or neonatal weight>90%ile.Results Data for a total of 2,650 SARS-CoV-2-positive pregnant women were available. The analysis was restricted to symptomatic cases that delivered after 24+0 weeks of gestation. Excluding those cases with missing values for estimated fetal weight at time of infection and/or birth weight centile, 900 datasets remained for analyses. Group I consisted of 551 women, Group II of 112 women, and Group III of 237 women. The percentage of changes from AGA to FGR did not differ between groups. However, there was a significantly higher rate of large for gestational age (LGA) newborns at the time of birth compared to the time of SARS-CoV-2 infection in Group III (p=0.0024), respectively.Conclusion FGR rates did not differ between symptomatic COVID infections occurring within 2 weeks and>4 weeks before birth. On the contrary, it presented a significant increase in LGA pregnancies in Group III. However, in this study population, an increase in the percentage of LGA may be attributed to pandemic measures and a reduction in daily activity.
Keywords: SARS-CoV-2; fetal growth restriction; large for gestational age; pregnancy; COVID-19; outcome